Non-conventional protein sources - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Traditional sources of protein take up a large part of the family budget in Third World countries, whether it be for feeding family members or livestock. It is thus of interest to investigate alternative sources of protein such as snails, frogs,...